Assement of Severity of Community Acquired Pneumonia By CURB-65 - Ahmed Talal Abdullah; Ismail Ibrahim Latif (Diyala Journal of Medicine, 2019)
Background:Community-acquired pneumonia. is a disease in which individuals who have not recently been hospitalized develop an infection of the lungs, which can affect people at all ages.  Pneumonia affecting about 2/1000 of the population per year.The initial assessment of the severity of community-acquired pneumonia is important for patient management. Severity assessment is an important early step in the management of patients presenting with community-acquired pneumonia. Various pneumonia-specific scores, generic sepsis scores and predictive biomarkers have been proposed as tools to aid clinicians in key management decisions.